Maternal Knowledge Level Determining Parenting Self-Efficacy of Low Birth Weight Babies: Pilot Study - Amaliya, Sholihatul; Harhara, Shifa Resti; Kapti, Rinik Eko; Azizah, Nurona; Novera, Dian (Universitas Airlangga, 2022)
Introduction: Low birth weight (LBW) babies have a higher risk of morbidity and mortality than normal babies, so this is a challenge for parents to provide special care. Mother's self-efficacy in providing care for LBW is an essential component in determining the quality of care of LBW. However, evidence is scarce on the correlation between the level of maternal knowledge and maternal self-efficacy in caring LBW, especially in Indonesia. Therefore, this study aimed to investigate the correlation between maternal knowledge level and maternal self-efficacy level who had LBW babies. Methods: The research design was a descriptive analysis involving 22 respondents of postpartum mothers with LBW, willing to be involved in research and able to read and write and had LBW babies treated in the perinatology ward of a state teaching hospital in East Java in January-March 2020. Data were collected using maternal knowledge questionnaire and perceived maternal parenting self efficacy (PMP-SE) questionnaire. The descriptive and gamma correlation test were analyzed in this research. Results: Spearman's rho correlation test showed a significant correlation between the level of knowledge and the mother's self-confidence (p = 0.043; r=0,435). Conculusion: : The level of knowledge determines the level of self-efficacy in caring LBW babies, where the higher the level of knowledge correlates with the higher maternal self-efficacy. Nurses need to understand mothers' self-efficacy with LBW babies because high self-efficacy can indicate that mothers can provide quality care for LBW babies